2018
DOI: 10.21037/qims.2018.08.09
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac balanced steady-state free precession MRI at 0.35 T: a comparison study with 1.5 T

Abstract: This study demonstrates that cardiac bSSFP imaging is highly feasible at 0.35 T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…The temporal resolution and scan time were matched across the three scanners, requiring slightly lower acquired spatial resolution at 0.35 T due to the lower gradient performance. Cine images acquired at 0.35 T with flip angles greater than 110° were shown recently by Rashid et al 27 to have comparable image quality with 1.5 T cine images with flip angle 90°. Based on this information, we set the flip angle at 110° for 0.35 T cine 27 .…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…The temporal resolution and scan time were matched across the three scanners, requiring slightly lower acquired spatial resolution at 0.35 T due to the lower gradient performance. Cine images acquired at 0.35 T with flip angles greater than 110° were shown recently by Rashid et al 27 to have comparable image quality with 1.5 T cine images with flip angle 90°. Based on this information, we set the flip angle at 110° for 0.35 T cine 27 .…”
Section: Methodsmentioning
confidence: 79%
“…Cine images acquired at 0.35 T with flip angles greater than 110° were shown recently by Rashid et al 27 to have comparable image quality with 1.5 T cine images with flip angle 90°. Based on this information, we set the flip angle at 110° for 0.35 T cine 27 . At 1.5 and 3 T, the flip angle was initially set to 90° and then reduced automatically to the maximum flip angle allowed by SAR limits for each subject to maximize blood‐myocardium contrast.…”
Section: Methodsmentioning
confidence: 79%
“…The decreased T 1 and specific absorption rate (SAR) at this field strength compared with higher fields of 1.5T and 3T can also be leveraged to optimize steady‐state sequences, particularly for SAR‐intensive applications such as cardiac imaging. These advantages have been demonstrated in the work by Rashid et al Balanced SSFP‐based imaging of the heart at 0.35T on an MRI‐guided radiation therapy system (MRIdian, ViewRay, OH) with an actively shielded superconducting magnet, split bore, and 18 mT/m gradients was compared with corresponding images from a standard 1.5T. This balanced (b)SSFP study demonstrated that image quality at 0.35T approached that seen at 1.5T at high flip angles.…”
Section: Current State Of the Artmentioning
confidence: 88%
“…Clinical MR for cardiac imaging typically uses 1.5 tesla (T) systems and, less commonly, 3T systems, despite the availability of higher field MRI. There are potential advantages to lower field (<1.5T) for cardiovascular applications, which has generated recent interest in low‐field cardiac MRI 1‐3 . Low field may offer reduced costs, reduced artifacts, and improved safety for cardiac imaging.…”
Section: Introductionmentioning
confidence: 99%
“…RF power scales quadratically with field strength, which leads to improved safety for cardiovascular implanted electronic devices and metallic devices used for MRI‐guided cardiovascular catheterization procedures 4,5 . The reduced specific absorption rate constraints also permit imaging with higher flip angles 2 . Increased main magnetic field (B 0 ) homogeneity at low field provides linear scaling of absolute susceptibility 6 .…”
Section: Introductionmentioning
confidence: 99%